Distributional and Fiscal Effects of the German Tax Reform 2000 : A Behavioral Microsimulation Analysis - Viktor Steiner; Peter Haan (Deutsches Institut für Wirtschaftsforschung (DIW), 2004)
In the year 2000, the German government passed the most ambitious tax reform in postwar German history aiming at a significant tax relief for households. Drawing on data of the GSOEP, we analyze the distributional and fiscal effects of the tax reform. Our analysis employs microsimulation techniques. Furthermore, we estimate behavioral effects of the tax reform using a discrete choice labor supply model. We find that the tax reform leads to a significant increase of net household income. The relative gains increase with taxable income, thus income inequality is rising. We also find that behavioral effects reduce the revenue loss.
Keywords: H31; J22; H24; 330; tax reform; behavioral effects; distribution and fiscal effects; Steuerreform; Steuerwirkung; Arbeitsangebot; Steuerinzidenz; Steueraufkommen; Schätzung; Deutschland; Mikrosimulation